Employment insertion strategies for prisoners and released prisoners through work cooperatives: The cases of Buenos Aires and Chaco in Argentina - Mayer, Natalia (Cooperativismo & Desarrollo, 2023)
In Argentina, spending time in prison aggravates the situation of exclusion of people due to the formal durability of 10 years of criminal records from the time of conviction. This article reviews the process of emergence of work cooperatives made up of prisoners and released prisoners as a strategy for labor and social inclusion, emphasizing the relationship they establish with the State and the creation of a new political identity. The empi-rical material analyzed was collected during the years 2020 and 2021. From a qualitative approach, virtual and face-to-face semi-structured interviews were conducted with referents and members of work cooperatives in the provinces of Buenos Aires and Chaco. The collected testimonies indicate that the actors use prison logic and experiences that group them together, and combining them with strategies from the popular economy, they fight to reverse stigmatization. In this way, they produce a political activism that emerges from prison as a place of enunciation to demand socio-labor inclusion from the State. Likewise, the strategy is successful as an alternative to overcome the employment crisis.